(untitled) (Research, Society and Development, 2021)
Objective: The aim of the study was to analyze the survival time of people diagnosed with an HIV infection and deaths with mention of HIV/AIDS, associated with antiretroviral therapy from 2008 to 2018, in residents in the region of Campos Gerais – Paraná. Methodology: It is a retrospective, exploratory and documentary cohort study. Results: The research consisted of 737 people, which 56.9% correspond to cases of death and 43.1% to living people diagnosed during the evaluation period. It was found that 59.3% were male, 77.6% of race and/or skin color white and 58.6% with elementary school. The median survival was 8.8 years, with women aged 10.2 years, illiterates aged 7.1 years and those over 60 years of age with 5 years of survival. It was also found that people living with HIV without using antiretrovirals had very low average survival, only 4.7 years. Despite the disparities between the subgroups evaluated, TARV has a significant impact on survival time when treatment is started early. Conclusion: Survival surveys make it possible to monitor imbalances in health care, treatment and care, situations that directly influence the quality and life expectancy of people living with HIV.